SISTEM INFORMASI DAN MANAJEMEN TAMAN PENDIDIKAN AL-QUR'AN IMAM SYAFI'I BANJARMASIN BERBASIS WEB - Fitri, Rahimi; Subandi, Subandi; Saberan, Saberan; Herlinawati, Herlinawati; Effendi, M. Iqbal; Fayruz, Nafila (Politeknik Negeri Banjarmasin, 2021)
TPQ Imam Syafi'I is one of TPQs that has a manual management and learning process, both from the student registration process which still using forms and attendance reports. The student learning outcomes are reported by the teacher and submitted to the administrator to be reported to the head of TPQ with the data obtained. The data obtained are stored in a record book or the form of a digital file in a spreadsheet which can allow for errors in entering data. Based on this problem, TPQ Imam Syafi'i Banjarmasin Management Information System was created based on a Web that uses PHP as a programming language and Laravel for the framework. With the final results obtained from this web system, there are four types of users as follows; Head of TPQ, Administrator, Teacher, and Student (Student Guardian)